y=9-2/9

Simple and best practice solution for y=9-2/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=9-2/9 equation:



y=9-2/9
We move all terms to the left:
y-(9-2/9)=0
We add all the numbers together, and all the variables
y-(-2/9+9)=0
We get rid of parentheses
y-9+2/9=0
We multiply all the terms by the denominator
y*9+2-9*9=0
We add all the numbers together, and all the variables
y*9-79=0
Wy multiply elements
9y-79=0
We move all terms containing y to the left, all other terms to the right
9y=79
y=79/9
y=8+7/9

See similar equations:

| (1*2+-5x*2)+4=-8 | | g+133/5=151/4 | | 330=2x150/5 | | 6x2+4x+1=0 | | 87=146r= | | 10x-3x=630 | | (3+x)=12-4x | | 8x-x=315 | | 8t=10(1/2t)+27 | | 3x–15=-2x+30 | | (133)=(9x+2) | | 26b+8-9=5 | | 8(2t)=10(t)+27 | | 3x-7)(9x+1)=0 | | 11x-(3x+4)+19=3x | | J(x)=-2+5 | | x2+14x+17x=96 | | -4+4x=2(-51+9x) | | 9x-24=6+7x | | 157=9x-14 | | 4t+2-t=8 | | x+1/12=1/3 | | x/45=12 | | 7(x)=49 | | 19v=57 | | 3(x-3)=2+3x | | x2+-5X-20=0 | | 17(10)^2x=136 | | 9x+36=6-6x | | 2r^2-20r-13=0 | | -4x+5=-13x+39=90 | | 5y+7=2y-3 |

Equations solver categories